2001
DOI: 10.1212/wnl.56.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cognitive impairment or decline in preclinical Alzheimer’s disease

Abstract: Pathologically confirmed preclinical AD is not associated with cognitive impairment or decline, even on measures shown to be sensitive to very mild DAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 44 publications
8
57
0
Order By: Relevance
“…It should be also noted that the disorganization of these higher order thinking abilities, which are related to fluid intelligence, was found to be present before the appearance of clinically detectable dementia in the participants in the sample of old-old adults. This result seems to be in line with findings indicating that a large proportion of healthy old-old adults shows memory decline which may represent the early stages of a potentially more severe cognitive impairment (Goldman et al, 2001;Shoji et al, 2002;Schmitt et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It should be also noted that the disorganization of these higher order thinking abilities, which are related to fluid intelligence, was found to be present before the appearance of clinically detectable dementia in the participants in the sample of old-old adults. This result seems to be in line with findings indicating that a large proportion of healthy old-old adults shows memory decline which may represent the early stages of a potentially more severe cognitive impairment (Goldman et al, 2001;Shoji et al, 2002;Schmitt et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…As regards the preclinical AD patients with neurological changes, it was reported that they do not demonstrate measurable cognitive decline on standard tests (Goldman, Price, Storandt, Grant, McKeel, Rubin, & Morris, 2001;Schmitt, Davis, Wekstein, Smith, Ashford, & Markesbery, 2000). More sensitive tests to detect early or preclinical stages of AD are desired, such as the MMSE, Wechler Adult Intelligence Scale-Revised (WAIS-R) and the Wechler Memory Scale-Revised (WMS-R), which are evidencebased test batteries for memory decline and intelligence.…”
mentioning
confidence: 99%
“…An early study of 633 participants found no incident AD cases over four years among individuals who reported use of vitamin E or C supplements at baseline [19], while an investigation of 3,385 men found reduced prevalence of vascular and mixed dementias, but not AD, among users of both vitamin E and C supplements [144]. These results contrast with one of the above-cited studies that showed no association between AD and antioxidant vitamin consumption in either dietary or supplement form [141].…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…Goldman et al [17] found no weakness in fluency in a group with confirmed pre-clinical AD when compared with healthy controls, but restricted their fluency measurement to production to two letters, and their MCI group was very small (n = 5). Lambon Ralph et al [29] found patients with MCI performed similarly to a control group on tasks of phonemic fluency; they did not, however, assess semantic fluency, which is more commonly depressed in AD.…”
Section: Introductionmentioning
confidence: 98%